Low-income and overweight in China: Evidence from a life-course utility model - Yanjun Ren; Bente Castro Campos; Jens-Peter Loy; Stephan Brosig (Journal of Integrative Agriculture, 2019)
Previous literature has demonstrated that low-income people are more likely to settle for poor health choices in developed countries. By using income as a budget constraint and signal for future wellbeing in a life-course utility model, we examine the association amongst income and overweight. The data used for this study are from the China Health and Nutrition Survey (CHNS). Estimations are conducted for overweight initiation, cessation, and participation mirroring a decision to begin and a past decision to not terminate. Our findings propose that body weight and the likelihood of overweight commencement rise with additional income but at a diminishing degree, representing a concave relation; while the likelihood of overweight discontinuance declines with additional income but at an accelerating degree, suggesting a convex relation. We presume that, as opposed to developed countries, low-income people are less inclined to be overweight in China, a country in transition. This could be explained by an income constraint for unhealthy foodstuff. Nevertheless, it will switch when income surpasses the critical threshold of the concave or inverted U-shape curve indicating that low-income people appear to receive not as much utility from future health. Specifically, this adjustment seems to occur earlier for females and inhabitants of urban areas.
Keywords: 330; low-income; overweight; life-course utility; China